Fundamental Approaches to Software Engineering 22nd International Conference, FASE 2019, Held as Part of the European Joint Conferences on Theory and Practice of Software, ETAPS 2019, Prague, Czech Republic, April 6-11, 2019, Proceedings - Hähnle, Reiner; van der Aalst, Wil (Theoretical Computer Science and General Issues, 2019)
This book is Open Access under a CC BY licence.